Selection of scFv phages on intact cells under low pH conditions leads to a significant loss of insert-free phages - Tur, M K (BioTechniques, 2001)
Display of functional antibody fragments on the surface of filamentous bacteriophages allows fast selection of specific phage antibodies against a variety of target antigens. However, enrichment of single chain variable fragment (scFv)-displaying phages is often hampered by the abundance of bacteriophages lacking antibody fragments. Moderate adhesive binding activities and production advantages of these "empty" phages results in their subsequent enrichment during selection on target cells. To date, very limited effort has been made to develop strategies removing nonspecific binding phages during the selection processes. To efficiently reduce insert-free phages when panning on intact cells, we increased the washing stringency by lowering the pH of the buffer with citric acid. Under standard washing procedures (pH 7.4), only approximately 73% of recovered phages were insert-free after three rounds of selection. Using stringent washing procedures (pH 5.0), approximately 12% of recovered phages contained no scFv. Using this protocol, we have cloned an antibody fragment from a mouse/human hybridoma cell line directed against the disialoganglioside GD2. This study confirms that selection of phage antibodies on cells is efficiently enhanced by assays augmenting the stringency to remove nonspecific binding phages